Outcomes for olfactory neuroblastoma treated with induction chemotherapy. Issue 8 (31st May 2017) - Su, Shirley Y.; Bell, Diana; Ferrarotto, Renata; Phan, Jack; Roberts, Dianna; Kupferman, Michael E.; Frank, Steven J.; Fuller, C. David; Gunn, G. Brandon; Kies, Merrill S.; Glisson, Bonnie S.; Hanna, Ehab Y.
Abstract: Background: Oncologic outcomes for induction chemotherapy and its role in patients with advanced olfactory neuroblastoma (ONB) remain unclear. Methods: A retrospective review of 15 consecutive patients with extensive local invasion and/or nodal disease treated with induction chemotherapy with curative intent followed by definitive local therapy. Results: The majority of patients were treated with cisplatin and etoposide. The response to chemotherapy was 68% (10/15). Response was 78% (7/9) in the high Hyams high‐grade group and 50% (3/6) in the Hyams low‐grade group. Seven patients had complete response (CR) and 3 patients were able to avoid orbital exenteration. The 5‐year disease‐free survival (DFS) and overall survival (OS) were 71% and 78%, respectively, with a trend toward improved survival in patients with CR. Conclusion: ONB is a chemosensitive tumor and induction chemotherapy is an acceptable strategy for aggressive and locoregional advanced disease. Hyams grade may predict chemosensitivity and CR may be associated with improved survival.